The Linear Relationship between Stock Returns and Interest Rates: Evidence from US Stock Markets - Zhou, Yuhong (2009)
The paper studies the linear relationship between stock returns and interest rates using a sample of US market from 2000 to 2008. The methodology of well tested Ordinary Least Square Model is applied. General results have showed a non-lagged significant positive and a one-day lagged significant negative correlation between returns and interest rates. And the presence of financial crisis is found to have dramatic influence on this specific correlation. In addition, the maturity term of interest rates are also found influential on this relationship.